Application of Nalbuphine in Trigeminal Ganglion Pulse Radiofrequency Surgery in Patients with Postherpetic Neuralgia. (2nd March 2021) - Wen, Song; Xiao, Qiu-Xia; Zhu, Zhao-Qiong; Chen, Li; Li, Ying; Ran, Qi-Hua; Cao, Song; Xiong, Liu-Lin
Abstract : This study aimed to explore the application value of nalbuphine in pulsed radiofrequency operation of trigeminal ganglion in patients with postherpetic neuralgia (PHN). Thirty patients with PHN were randomly divided into the nalbuphine (Nalbu) group and ketorolac tromethamine (KT) group and received CT-guided pulsed radiofrequency surgery on trigeminal ganglion. The numeric rating scale (NRS) scores of patients were recorded at preoperative, intraoperative, and postoperative time points, before going to bed, and the next morning after the operation. In addition, the number of breakthrough pain before operation and within 24 hours after operation, the incidence of nausea and vomiting within 24 hours after surgery, and the patient's sleep quality before and on the day after surgery were evaluated. The outcome data demonstrated that patients treated with nalbuphine had lower NRS scores after the pulse radiofrequency operation during and after the pulse radiofrequency operation compared to those with KT. In addition, nalbuphine effectively decreased the number of breakthrough pain, reduced the occurrence of nausea and vomiting after surgery, and improved the sleep quality. In conclusion, intramuscular injection of nalbuphine 30 min before trigeminal ganglion pulse radiofrequency surgery can be conducive to pain relief and improve the postoperative comfort of patients, providing an effective alternative for the alleviation of PHN in clinic.